2010
DOI: 10.1161/strokeaha.109.566596
|View full text |Cite
|
Sign up to set email alerts
|

Segment-Specific Associations of Carotid Intima-Media Thickness With Cardiovascular Risk Factors

Abstract: Background and Purpose-We propose to study possible differences in the associations between risk factors for cardiovascular disease (myocardial infarction and stroke) and carotid intima-media thickness (IMT) measurements made at 3 different levels of the carotid bifurcation. Methods-We conducted a cross-sectional study of a cohort of whites and blacks of both genders with a mean age of 45 years. Traditional cardiovascular risk factors were determined in cohort members. Carotid IMT was measured from high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 41 publications
10
111
3
6
Order By: Relevance
“…In an earlier report from the CARDIA study that used data from both men and women, cardiovascular risk factors explained a larger proportion of the CCA-IMT variability (26.8%) than the bulb (11.2%) or ICA (8.0%). 32 Furthermore, in The Vascular Aging (EVA) study, systolic blood pressure and hypertension were associated with both CCA-IMT and plaques at the Bulb and ICA; however, diabetes mellitus, lowdensity lipoprotein cholesterol, and high-density lipoprotein cholesterol were associated only with CCA-IMT. 33 Similarly, among Taiwanese women, the metabolic syndrome was only associated with CCA-IMT, but not with the bulbar or ICA-IMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier report from the CARDIA study that used data from both men and women, cardiovascular risk factors explained a larger proportion of the CCA-IMT variability (26.8%) than the bulb (11.2%) or ICA (8.0%). 32 Furthermore, in The Vascular Aging (EVA) study, systolic blood pressure and hypertension were associated with both CCA-IMT and plaques at the Bulb and ICA; however, diabetes mellitus, lowdensity lipoprotein cholesterol, and high-density lipoprotein cholesterol were associated only with CCA-IMT. 33 Similarly, among Taiwanese women, the metabolic syndrome was only associated with CCA-IMT, but not with the bulbar or ICA-IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Free and total testosterone measures were assessed using stored samples from CARDIA Year 2 (ages [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] by the OB/GYN Research and Diagnostic Laboratory at the University of Alabama, Birmingham. Total testosterone was measured using a competitive immunoassay (Beckman Coulter, Fullerton, CA) using direct chemiluminescent technology on the Beckman Access Automated System.…”
Section: Definition Of Characteristics Of Pcosmentioning
confidence: 99%
“…men and women and further controlled for conventional cardiovascular risk factors and habitual physical activity (PA). 16 Carotid IMT was measured at the level of common carotid artery (CCA) because previous studies have demonstrated that traditional risk factors 17 and metabolic variables 18 account for a greater proportion of IMT variability in the CCA than in the carotid bulb or internal carotid artery, and that the reproducibility of measurements is better for CCA than for other carotid segments. 19 The presence of plaques, however, was evaluated in the entire extracranial carotid tree as one of the first and the most common site of early atherosclerotic plaque formation is carotid bifurcation.…”
mentioning
confidence: 99%
“…Polak et al [17] showed that FPG and diastolic BP had a stronger association with CIMTc while hypertension, diabetes, and smoking with CIMTb.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of CIMT includes evaluation of common carotid artery (CIMTc), bifurcation (bulb; CIMTb), and internal carotid artery and it has been shown that the association of the CIMT with CV risk factors varies according to the segment assessed [17]. The association between CIMT and NAFLD has been reported in the past years and this association was independent of other CV risk factors [18,19].…”
Section: Introductionmentioning
confidence: 99%